Projeções populacionais para pequenas áreas a partir de cenários econômicos: aplicação de ratio methods para a região do Alto Paraopeba-MG, 2010-2025 - Reinaldo Onofre dos Santos (2010)
The main objective of this paper is to present an alternative and objective methodology that meets the growing demand for population scenarios at the micro-scale. The interest in projecting population of small areas comes from the difficulty of making estimates based on conventional methods such as the Demographic Components. Moreover, the interest of planners on the use of techniques more sensitive to migration, a demographic component that responds more quickly to regional economic fluctuations, is also noteworthy. The region of Alto Paraopeba in Minas Gerais is adopted as a case study. The region will receive, in the next fifteen years, investments of over twenty billion reais in the mining and steel sectors. The employments generated by these investments will be strong drivers of income and regional population expansion, serving as motivation for people moving from other regions. Therefore, the effects of these investments will be translated into demographic changes, with the expansion of immigration and, thus population growth. The investments will change the pattern of regional development imposing to regional planners the challenge of meeting growing populations with services and infrastructure. Thus, this work has elaborated projections for the region and its municipalities based on techniques sensitive to economic changes in order to subsidize public authorities with knowledge about the demographic future of the region. With this goal, we will discuss the usefulness of a set of projection techniques of small areas known as ratio methods. Their construction meets the condition of return, i.e., equality between the projections of population for a large area and the sum of its small area constituents. These techniques have the advantage of using a projection process for a large area and, based on some criteria, divide the population growth among smaller areas. Thus, a population projection for the area was constructed using the component method together with the technique AiBi for the projection of small areas. From the regional employment projections, we applied the P/E method (FÍGOLI et al, 2007) to estimate the effects of regional employment. Then, we used the conventional ratio methods in comparison with the adjusted AiBi proposed by Barbieri (et al, 2010) and the two-stage partition used in this work. Results show that, in general, ratio of projection methods are trend projection tools calling for adjustments in order to introduce greater sensitivity to economic scenarios. The adjusted AiBi method offers sensitivity-related advantages, but given their subjective nature jeopardizes the replicability in other contexts. The partitioning of two stages, considering the trend scenario and the effect of economic swings aside, offers greater objectivity and replicability, and results more fine-turned with the scenarios subjected to prediction. Anyway, the Upper Paraopeba is expected to experience a population growth exceeding 65% in the next fifteen years, which will require special attention regarding the regional spatial planning in the short and medium terms, besides explaining the temporal and spatial studies of Demography Applied to Planning Regional